Risk factors of uterine prolapse in a sample of rural women of central Nepal - Manandhar, Pratima; Rai, Sirjana Kumari (Journal of Kathmandu Medical College, 2022)
Background: In Nepal, 9-35% of Nepali women suffer from uterine prolapse, and 200,000 are in need of immediate surgical treatment. Objectives: To assess risk factors of uterine prolapse among women of Hariharpurgadhi-2, Sindhuli district, Nepal. Methods: This community-based analytical cross-sectional study was conducted among 60 married women of Hariharpurgadhi-2, Sindhuli district, which is central rural area of Nepal. Samples were selected through snowball sampling technique. In the sample, the women who have been diagnosed with uterine prolapse and interested were included. Data were collected during 2020 January 20th to 2020 February 24th, through face-to-face interview method using structured interview schedule questionnaire which included structured and semi-structured questions. Collected data were analysed in SPSS v.16 by using descriptive and inferential statistics. Results: The study found 21 (35%) respondents had first degree uterine prolapse. One-fifth (15, 25%) of them had asthma, 46 (76.7%) had constipation, 26 (43.3%) had chronic cough, 19 (31.7%) had reproductive infection, and 23 (38.3%) of them were smoker. The degree of uterine prolapse was significantly associated with marriage <20 years (p = 0.004), first childbirth <20 years (p = 0.01), higher the number of pregnancy (p = 0.007), and higher the number of childbirth (p = 0.007). Conclusion: The study findings show that marriage age of below 20 years, first childbirth age of below 20 years, higher number of pregnancy, and higher number of childbirth were the major factors for uterine prolapse. Therefore, public awareness on these factors would be the first step to reduce uterine prolapse.